Ethics of Thinking in the Era of Artificial Intelligence: (A Comparative Analysis of Fakhruddin al-Rāzī and Quraish Shihab on Q.S. Al-Isrā’ (17): 36) - Khobir; Azhar nasution (Institut Agama Islam Sumatera Barat, 2026)
The massive integration of Artificial Intelligence (AI) into Islamic education and Quranic studies has triggered an epistemic crisis in the form of the degradation of intellectual authority and the erosion of spiritual values. This research aims to formulate a framework for Quranic thinking ethics in the AI era through a thematic analysis of Surah Al-Isrā’ verse 36 from the perspectives of Fakhruddin al-Rāzī and Quraish Shihab. This qualitative study employs a library research method with a comparative-hermeneutical approach. The primary sources used are Mafātīḥ al-Ghayb (Volume 20) and Tafsīr al-Mishbāh (Volume 7), supported by secondary data from contemporary journals on AI and Islamic ethics. The results indicate that al-Rāzī emphasizes the moral-rational dimensions of epistemic tools (hearing, sight, and the heart) as a divine trust (amanah), while Quraish Shihab focuses on social-intellectual responsibility in navigating the modern flow of information. The synthesis of these two perspectives produces the concept of